2018
DOI: 10.15252/embr.201745471
|View full text |Cite
|
Sign up to set email alerts
|

Map7/7D1 and Dvl form a feedback loop that facilitates microtubule remodeling and Wnt5a signaling

Abstract: The Wnt signaling pathway can be grouped into two classes, the β-catenin-dependent and β-catenin-independent pathways. Wnt5a signaling through a β-catenin-independent pathway promotes microtubule (MT) remodeling during cell-substrate adhesion, cell migration, and planar cell polarity formation. Although Wnt5a signaling and MT remodeling are known to form an interdependent regulatory loop, the underlying mechanism remains unknown. Here we show that in HeLa cells, the paralogous MT-associated proteins Map7 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…MAP7D3 can be rapidly relocalized to MT plus ends by overexpressed K560, but at the endogenous kinesin-1 expression levels, MAP7D3 is not enriched at MT plus ends, suggesting that the levels of endogenous motor are insufficient to drive MAP7D3 to the cell periphery. Still, it is possible that also the endogenous kinesin-1 could cause some redistribution of its own positive regulators, which would be in line with some previous observations (Kikuchi et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…MAP7D3 can be rapidly relocalized to MT plus ends by overexpressed K560, but at the endogenous kinesin-1 expression levels, MAP7D3 is not enriched at MT plus ends, suggesting that the levels of endogenous motor are insufficient to drive MAP7D3 to the cell periphery. Still, it is possible that also the endogenous kinesin-1 could cause some redistribution of its own positive regulators, which would be in line with some previous observations (Kikuchi et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…1A, B). Gene expression analysis at the mRNA and protein level indicated that HeLa cells co-express MAP7, MAP7D1 and MAP7D3 (Kikuchi et al, 2018;Syred et al, 2013), and we confirmed these data by antibody staining (Fig. 1C).…”
Section: Map7 Family Members Act Redundantly In Mitochondrial Distribsupporting
confidence: 85%
“…Map7/7D1 binds to Dvl and modulates MT remodeling in HeLa cells, whereas Map7/7D1 knockdown impaired MT plus-end cortical targeting and focal adhesion turnover. Furthermore, Map7/7D1 promotes the cortical targeting of Dvl in response to Wnt5a, providing further support to the role of Dvl in cell migration dynamics during Wnt5a signaling (Kikuchi et al, 2018). However, it must be stressed that the specific relevance of these findings for gastric cancer remains to be fully explored.…”
Section: Wnt5a In Gastric Cancer: Molecular Mechanismsmentioning
confidence: 80%